2011
DOI: 10.1007/s11010-010-0707-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of fatty acid synthase, differentiation and lipid accumulation in adipocytes by curcumin

Abstract: Curcumin is a well-known component of the cook seasoning and traditional herb turmeric (Curcuma longa), which has been reported to prevent obesity. However, the mechanism still remains to be determined. In this study, curcumin is found to be an effective inhibitor of fatty acid synthase (FAS), and its effects on adipocytes are further evaluated. Curcumin shows both fast-binding and slow-binding inhibitions to FAS. Curcumin inhibits FAS with an IC₅₀ value of 26.8 μM, noncompetitively with respect to NADPH, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 24 publications
3
65
1
1
Order By: Relevance
“…Furthermore, curcumin treatment along with high-fructose diet down-regulated the hepatic expression of ACC and FAS. Curcumin competitively binds to malonyl/acetyl transferase domain and covalently modifies FAS thereby decreasing TAG synthesis (Zhao et al 2011). Another study reported that curcumin inhibits hepatic lipogenesis through down-regulation of SREBP1c expression (Shao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, curcumin treatment along with high-fructose diet down-regulated the hepatic expression of ACC and FAS. Curcumin competitively binds to malonyl/acetyl transferase domain and covalently modifies FAS thereby decreasing TAG synthesis (Zhao et al 2011). Another study reported that curcumin inhibits hepatic lipogenesis through down-regulation of SREBP1c expression (Shao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…HDL-cholesterol is good for health, since it facilitates mobilization of triglycerides and cholesterol from the plasma to the liver [55]. Curcumin decreases the expression of FAS, a key enzyme in the de novo long-chain FA synthesis pathway [56]. Moreover, curcumin enhanced FA β-oxidation in adipocytes with a concomitant increase in the expression of CPT-1, a key enzyme in transferring acyl-CoA into mitochondria for β-oxidation [57].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of curcumin, the major polyphenol found in turmeric, to rodent models of obesity has been shown to reduce body weight gain and ameliorate the development of diabetes (123,124) . This is thought to be due to its ability to suppress adipocyte differentiation and indeed this has been found in studies using the murine 3T3-L1 cell line, with a concomitant downregulation of PPARg (125,126) ; however, in another study utilising 3T3-L1 cells, these transcriptional markers were not affected (124) . A recent comprehensive investigation into the ligand activity of curcumin found it to have no binding activity at the PPARg ligand-binding site and subsequently no effect on adipocyte differentiation (127) .…”
Section: Adipocyte Hypertrophymentioning
confidence: 90%